Un método efectivo y económico de extracción de ADN en la radícula embrionaria de semillas de guandú (Cajanus cajan) adecuado para análisis por PCR (Bioagro, 2024)
The presence of co-extracted impurities in seeds can make DNA extraction challenging, as these contaminants can interfere with PCR amplification, both of which, extraction and PCR, are important steps for ongoing breeding and selection programs. A new protocol is evaluated in this study as an alternative for extracting DNA from embryonic radicle tips of pigeonpea seeds that yield DNA readily amenable to PCR. The proposed protocol for DNA extraction in pigeonpea seeds shows great promise as an alternative method, as it is low-cost, straightforward, and effective for PCR amplification. It also has the advantage of not requiring hazardous or expensive reagents and can be easily scaled up, demonstrating its potential as a valuable resource for scientists studying pigeonpea genetics and breeding.
Keywords: Amplificación por PCR; guandú; marcadores moleculares; método HotSHOT; rendimiento de ADN